2010
DOI: 10.1176/ps.2010.61.12.1239
|View full text |Cite
|
Sign up to set email alerts
|

Medication Adherence and Hospitalization Among Patients With Schizophrenia Treated With Antipsychotics

Abstract: Results document rates of antipsychotic adherence and predictors of nonadherence and hospitalization. Findings may be useful to health plan administrators, formulary decision makers, and physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 24 publications
5
44
1
2
Order By: Relevance
“…It should be noted, however, that in this study, patients with awareness of their illness were also more likely to have other characteristics that may contribute to nonadherence, including substance abuse and sensitivity to the stigma associated with taking antipsychotic medication 29. In the aforementioned study that surveyed 699 psychiatrists,2 stigma was the barrier to adherence most frequently described by patients, and research has shown that substance abusers are at a significantly higher risk for medication nonadherence compared with nonusers 9. A team approach to support adherence and overcome barriers to nonadherence is therefore essential in all patients, although the type and intensity of the intervention may vary based on the characteristics of the individual patient.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…It should be noted, however, that in this study, patients with awareness of their illness were also more likely to have other characteristics that may contribute to nonadherence, including substance abuse and sensitivity to the stigma associated with taking antipsychotic medication 29. In the aforementioned study that surveyed 699 psychiatrists,2 stigma was the barrier to adherence most frequently described by patients, and research has shown that substance abusers are at a significantly higher risk for medication nonadherence compared with nonusers 9. A team approach to support adherence and overcome barriers to nonadherence is therefore essential in all patients, although the type and intensity of the intervention may vary based on the characteristics of the individual patient.…”
Section: Resultsmentioning
confidence: 67%
“…In a patient survey study that was conducted by nurses, the two most prominent barriers to medication adherence were stigma associated with taking medication and adverse drug reactions 2. Evidence also suggests that a variety of other factors may play a role in pharmacotherapy nonadherence among patients with schizophrenia, including the drug class prescribed (ie, typical versus atypical antipsychotics),35 drug formulation (ie, oral versus long-acting injectable [LAI] formulation),6 lack of adequate social support,7 lack of access to health care,8 and concurrent substance abuse 9. In patients with schizophrenia, nonadherence to prescribed medication is associated with symptom relapse, increased hospitalizations, and increased health care costs 10,11…”
Section: Introductionmentioning
confidence: 99%
“…[46] The influence of family on compliance is a modifiable factor which can be achieved through psychoeducation. [114849] Implementation of this measure is beset with operational difficulties in countries with limited workforce. Stigma of mental illness affecting compliance and noncompliance has been reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Poor treatment adherence is one of the strongest predictors of relapse and hospitalization 1518. It has been linked to lack of insight into illness,3,19 use of first-generation antipsychotics instead of second-generation antipsychotics,20 poor therapeutic alliance,19,21 comorbid substance use,19,21,22 poor treatment efficacy,23 and treatment tolerability issues 23. Understanding and improving early treatment adherence may improve longer-term outcomes.…”
Section: Introductionmentioning
confidence: 99%